2016
DOI: 10.1055/s-0036-1579781
|View full text |Cite
|
Sign up to set email alerts
|

Feeling Normal? Long-Term Follow-up of Patients with a Cleft Lip–Palate after Rhinoplasty with the Derriford Appearance Scale (DAS-59)

Abstract: The stigma of nasal deformity due to a congenital cleft lip-palate has an undeniable influence on the affected patient's life. It is therefore of interest to investigate if efforts to reduce esthetic and functional impairments by rhinoplasty (single or multiple) can result in an increased satisfaction with appearance and a self-perception similar to the noncleft population. Retrospective scoring before and after rhinoplasty using the validated Derriford Appearance Scale (DAS-59) and subsequent statistical eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The age of 13 was chosen for minimum age inclusion criteria, similar to a study by Pagan and colleagues, to include those patients who undergo secondary rhinoplasty in adolescence and have also reached permanent dentition. [9][10][11][12][13][14][15] Post hoc analysis was later performed on this subset of patients who had undergone a secondary rhinoplasty.…”
Section: Patient Selection and Analysismentioning
confidence: 99%
“…The age of 13 was chosen for minimum age inclusion criteria, similar to a study by Pagan and colleagues, to include those patients who undergo secondary rhinoplasty in adolescence and have also reached permanent dentition. [9][10][11][12][13][14][15] Post hoc analysis was later performed on this subset of patients who had undergone a secondary rhinoplasty.…”
Section: Patient Selection and Analysismentioning
confidence: 99%
“…The findings from two systematic reviews (Hunt et al, 2005;Al-Namankany and Alhubaishi, 2018) and one narrative review (Stock and Feragen, 2016) indicate that two key issues that often emerge are dissatisfaction with facial appearance and speech. While some research has found no difference in appearance satisfaction between cleft and noncleft groups (Albers et al, 2016), or even higher appearance satisfaction in the former group (Berger and Dalton, 2009), young people with CL/P often report lower appearance and speech satisfaction compared to noncleft control groups (Hunt et al, 2006;Van Lierde et al, 2012;Wehby et al, 2012). Appearance and speech dissatisfaction can impact several major domains of psychosocial functioning, including self-esteem, mental health, and quality of life (Stock and Feragen, 2016).…”
Section: Appearance and Speech Satisfactionmentioning
confidence: 99%
“…The American Academy of Pain Medicine notes that the burden of pain is felt in various components of everyday life and quantifies productivity losses as a consequence of it [ 25 ]. Similarly, perceived esthetic compromise is reportedly associated with anxiety and depression in children and adolescents; it is easily extrapolated to adults, especially in light of long-term studies of patients with craniofacial abnormalities which elucidate results of lower facial esthetics in adulthood [ 26 , 27 ]. It is therefore understandable how poor oral health could contribute to a social self-consciousness, having its endpoints in sexual and emotional fields.…”
Section: Discussionmentioning
confidence: 99%